2019
DOI: 10.4103/aja.aja_119_18
|View full text |Cite
|
Sign up to set email alerts
|

The role of tumor size, ultrasonographic findings, and serum tumor markers in predicting the likelihood of malignant testicular histology

Abstract: The clinical predictive factors for malignant testicular histology remain unclear because of the low prevalence. Therefore, the aim of this study was to investigate predictors of malignant histology for testicular masses and decide more testis-sparing surgeries before surgery. This retrospective study enrolled 325 consecutive testicular mass patients who underwent radical orchiectomy (310/325) or testicular preserving surgery (15/325) from January 2001 to June 2016. The clinicopathological factors, including t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 16 publications
0
19
1
Order By: Relevance
“…Putatively, ethnic and geographic differences of the various populations studied can also explain the variation of marker elevation rates among the reported studies. Accordingly, in a recent cohort of Chinese GCT patients, prevalence rates of elevated bHCG levels and AFP-levels were reported to be as high as 70% and 48%, respectively [48]. Yet, these data show that the over-all frequency of tumour marker elevation is less than 50% regarding all GCT patients at least in those of Caucasian descent and even the elevation rate of any of the markers is encountered in less than 60%.…”
Section: Discussionmentioning
confidence: 99%
“…Putatively, ethnic and geographic differences of the various populations studied can also explain the variation of marker elevation rates among the reported studies. Accordingly, in a recent cohort of Chinese GCT patients, prevalence rates of elevated bHCG levels and AFP-levels were reported to be as high as 70% and 48%, respectively [48]. Yet, these data show that the over-all frequency of tumour marker elevation is less than 50% regarding all GCT patients at least in those of Caucasian descent and even the elevation rate of any of the markers is encountered in less than 60%.…”
Section: Discussionmentioning
confidence: 99%
“…Colour Doppler by its qualitative nature is difficult to quantify. While some authors 11 have included arbitrary colour flow scores, colour Doppler does not usually play a role in urological workup at present apart from the binary observation of the presence or absence of vascularity 3 . Contrast‐enhanced US, 29 sonoelastography 16,30 and 3D 31 are showing some promise for the future, but these techniques are better suited for research purposes and are not readily available in clinical use to the majority of practitioners in Australasia.…”
Section: Discussionmentioning
confidence: 99%
“…There is a certain degree of misdiagnosis and missed diagnosis for metastatic melanoma in vivo . Combining with a serum tumor marker can better improve the diagnostic efficiency[27,28]. Logistic single- and multiple-factor analyses showed that TNM stage, miR-489, and miR-21 were independent risk factors for melanoma metastasis.…”
Section: Discussionmentioning
confidence: 99%